A brief history of oocyte cryopreservation: Arguments and facts. (25th March 2019) - Iussig, Benedetta; Maggiulli, Roberta; Fabozzi, Gemma; Bertelle, Sara; Vaiarelli, Alberto; Cimadomo, Danilo; Ubaldi, Filippo M.; Rienzi, Laura
Abstract: The term "cryopreservation" refers to the process of cooling cells and tissues and storing them at subzero temperatures in order to stop all biological activity and preserve their viability and physiological competences for future use. Cooling to subzero temperatures is not a physiological condition for human cells; this is probably due to the high content of water in the living matter, whose conversion to ice crystals may be associated with severe and irreversible damage. Among reproductive cells and tissues, metaphase II oocytes are notably vulnerable to cryopreservation, mainly because of their large size, low surface area to volume ratio, relatively high water content and presence of the meiotic spindle. As human biological systems lack efficient internal defense mechanisms against chilling injuries, it is of the utmost importance to supply adequate external support, in terms of cryoprotectant additives, appropriate cooling/warming rates, and suitable long‐term storage. Over the years, scientists have proposed different cryopreservation strategies in the effort to achieve an optimized recipe ensuring cell survival and, at the same time, maintenance of the physiological functions and abilities necessary to continue life. However, despite the first success obtained in the 1980s with frozen oocytes, it was not until recently that notable improvements in the cryopreservation technique, thanks to the advent of vitrification, allowed a breakthrough of this fine procedure.